UiTM Malaysia route planner / Mohamad Yunus Mohamed Nasir - Mohamed Nasir, Mohamad Yunus (2008)
Route planner is a connecting route between a starting point and a point of destination, wherein the starting point, point of destination and connecting route. Route planner addresses the question of how "best" to go from point A to point B. The shortest route is most appropriate than others because it can save time, cost and effort. The Route Planner's core is Dijkstra's shortest-path-finding algorithm, with extensions for time dependent delays and paths constrained by travel mode. The internal network and trip requests are given to the path-finding algorithm, which creates routes and outputs them in the form of plans. The problem is, now a days there are many available routes that user can choose from Shah Alam to UiTM Malaysia. So, for the users, they may know or not which is the shortest route to follow. The objectives of this research/project are to provide information and guidance for users to find shortest path from familiar point or places to main entrance UiTM Malaysia by using car, to provide an approximation of the shortest distance between source and destination using Dijkstra's algorithm and to develop web based system UiTM Malaysia Route Planner for users who is familiar in Shah Alam.